E3-cordial graphs - Cahit, I; Yilmaz, R (Charles Babbage Res Ctr, 2000)
In this paper generalization of edge-cordial labellings are introduced and studied for special classes of trees and graphs.
Keywords: Cordial Graphs; Graceful